Numerical simulation of the regularized long wave equation by He's homotopy perturbation method - İnç, Mustafa; Ugurlu, Yavuz (Elsevier, 2007)
In this Letter, we present the homotopy perturbation method (shortly HPM) for obtaining the numerical solution of the RLW equation. We obtain the exact and numerical solutions of the Regularized Long Wave (RLW) equation for certain initial condition. The initial approximation can be freely chosen with possible unknown constants which can be determined by imposing the boundary and initial conditions. Comparison of the results with those of other methods have led us to significant consequences. The numerical solutions are compared with the known analytical solutions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: RLW equation; Homotopy perturbation method